SCY-078 Demonstrates Significant Tissue Penetration in Rats and Mice Following Oral or IV Administration. (4th October 2017) - Barat, Stephen; Borroto-Esoda, Katyna; Angulo, David
Abstract: Background: The ability of a pharmacologic agent to reach target organ(s) in therapeutically-meaningful concentrations is one of the fundamental considerations when developing effective, anti-infective treatments. SCY-078 is a novel, oral and intravenous (IV), triterpenoid glucan synthase inhibitor with activity against Aspergillus and Candida, currently in clinical development for the treatment of invasive fungal infections. Tissue distribution studies were conducted in rats and mice to evaluate the distribution profile of SCY-078 following oral or IV administration. Methods: Sprague-Dawley rats were given single oral doses of 3 H-SCY-078 at 5 mg/kg. Han Wistar and Long Evans (pigmented) rats were given single oral doses of 14 C-SCY-078 at 15 mg/kg or IV at 5 mg/kg. Mice were orally-dosed at 3, 6.25, 12, 25, 50, 100 mg/kg BID for seven days. Results: SCY-078 distributed rapidly into tissues following administration. In rats, Tmax in whole blood, plasma and tissues following oral dosing was 4 hours. Blood to plasma ratio was < 1.0 indicating low partitioning into erythrocytes. The tissue distribution profile in rats was generally consistent between IV and oral routes and between pigmented and non-pigmented strains. High concentrations were noted in pituitary, spleen, liver, adrenals, lymph nodes, thyroid, bone marrow, thymus, lungs, kidneys and vagina. Tissue:blood ratios in rats ranged from approximately 15- to 50-fold, indicating appreciable penetration characteristics. In mice, kidney concentrations were approximately 20-fold greater than plasma at all doses studied, and the kidney:plasma ratio increased in a dose-related fashion indicating enhanced tissue distribution from greater unbound fractions in plasma. In lungs, exposures in epithelial lining fluid were generally 4-fold greater than plasma and the epithelial lining fluid:plasma ratio increased as much as 13-fold. Concentrations in vaginal tissue and secretions also exceeded those in plasma, and increased as much as 10-fold. Conclusion: SCY-078 demonstrates significant tissue penetration, indicating an intrinsic ability to reach clinically meaningful levels in various potential target organs of importance, suggesting therapeutic benefit for both treatment and prophylaxis of invasive fungal infections. Disclosures: S. Barat, Scynexis, Inc: Employee, Salary; K. Borroto-Esoda, Scynexis Inc: Consultant, Consulting fee; D. Angulo, Scynexis, Inc: Employee, Salary